2013
DOI: 10.1089/ten.tea.2012.0333
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional-Engineered Matrix to Study Cancer Stem Cells and Tumorsphere Formation: Effect of Matrix Modulus

Abstract: Maintenance of cancer stem cells (CSCs) is regulated by the tumor microenvironment. Synthetic hydrogels provide the flexibility to design three-dimensional (3D) matrices to isolate and study individual factors in the tumor microenvironment. The objective of this work was to investigate the effect of matrix modulus on tumorsphere formation by breast cancer cells and maintenance of CSCs in an inert microenvironment without the interference of other factors. In that regard, 4T1 mouse breast cancer cells were enca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
71
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(77 citation statements)
references
References 84 publications
(98 reference statements)
6
71
0
Order By: Relevance
“…19 Similar to results from other studies discussed earlier, 17 CSC marker expression was time-dependent, peaking at 8 days of culture. 19 In another study, alginate beads with soft (21 kPa), moderate (70 kPa) and hard (105 kPa) stiffness were generated by changing alginate concentration and used to study the effect of 3D matrix stiffness on the biological characteristics of CSCs from human head and neck squamous cell carcinoma (HNSCC). 62 The authors found that significant CSC enrichment as well as gene expression of stemness markers was achieved in the alginate beads with moderate matrix stiffness.…”
Section: Biomaterials For Csc Growthsupporting
confidence: 85%
See 4 more Smart Citations
“…19 Similar to results from other studies discussed earlier, 17 CSC marker expression was time-dependent, peaking at 8 days of culture. 19 In another study, alginate beads with soft (21 kPa), moderate (70 kPa) and hard (105 kPa) stiffness were generated by changing alginate concentration and used to study the effect of 3D matrix stiffness on the biological characteristics of CSCs from human head and neck squamous cell carcinoma (HNSCC). 62 The authors found that significant CSC enrichment as well as gene expression of stemness markers was achieved in the alginate beads with moderate matrix stiffness.…”
Section: Biomaterials For Csc Growthsupporting
confidence: 85%
“…For example, Yang et al used an inert polyethylene glycol with a range of modulus of 2.5-70 kPa to study the effect of stiffness on CSC marker expression and tumor spheroid formation. 19 Results showed that the gel modulus had a strong bimodal effect on the tumor spheroid formation and the expression of CSC markers: cells encapsulated in the gel with modulus of 5.3 kPa had the highest growth rate and formed the largest and highest number of tumor spheroids, further exhibiting the highest expression of CSC markers. 19 Similar to results from other studies discussed earlier, 17 CSC marker expression was time-dependent, peaking at 8 days of culture.…”
Section: Biomaterials For Csc Growthmentioning
confidence: 96%
See 3 more Smart Citations